Modified training drills in improving the dribbling agility of futsal athletes - Marcojos, Ma. Jan Donna G.; Labastida, Mylene P.; Soriano, Jade Rona S.; Degracia, Jennifer; Urboda, Marinila T.; Gula, Louie P. (Frontiers in Complex Systems, 2025)
IntroductionFutsal has become increasingly popular over the years; hence, studies focusing on the integration of drills to improve the performance of athletes are relevant. This study investigates the impact of modified training drills in improving the dribbling agility of futsal athletes.MethodsA total of 13 athletes participated in the research. Their dribbling agility was classified based on the Test of Agility in Dribbling before and after the training duration. The training program, which follows the FITT principle, consisted of three sessions per week (following a TThS schedule) for 2 weeks, adapting their normal training days. Descriptive statistics (frequency counts, percentages, mean, and standard deviation) summarized the demographic characteristics and agility levels. A Wilcoxon signed-rank test was utilized to determine the significant difference between the pre-test and post-test results, as the participants were not randomly sampled. A Spearman's rank correlation test was used to test the association of demographic profiles with the levels of dribbling agility.ResultsDemographic analysis revealed that most participants were 14 years old, with a majority having a height between 140-149 cm and a weight of 40-49 kg. Descriptive statistics showed a significant improvement in agility performance, as the average agility time decreased from 24.51 s in the pre-test to 20.50 s in the post-test. After training, the participants’ dribbling agility levels shifted from predominantly ‘poor’ classifications to ‘average’, ‘good’, and ‘excellent’. Statistical analysis confirmed that this difference was statistically significant (p < 0.05). Further analysis revealed that weight has a significant association with agility performance, while age and height did not.DiscussionThe results support the hypothesis that modified training drills positively impact agility. The findings suggest that weight can be considered an important factor in evaluating the impact of agility training.ConclusionThe modified agility training program effectively enhanced dribbling agility among futsal athletes. The study suggests that future researchers may extend the training duration and control external factors. It is also recommended that weight be considered in planning and evaluating agility training programs.